Fiscal deficit, macro-uncertainty, and growth in Argentina - Jorge C. Avila (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2011)
We analyze the relationship between fiscal deficit, macroeconomic uncertainty and growth for the period 1915-2006, and conclude that the deficit, possibly through the volatility in relative prices it generates, is a significant restriction on per-capita income growth in Argentina.
Keywords: 330; Wirtschaftswachstum; Haushaltsdefizit; Risiko; Volatilität; Argentinien